Analisis Yuridis Putusan Dispute Settlement Body The World Trade Organization Tentang Kebijakan Larangan Ekspor Bijih Nikel Oleh Indonesia Dikaitkan Dengan Prinsip Kedaulatan Negara - Maharani, Elika; H.Z, Evi Deliana; Jayakusuma, Zulfikar (Jurnal Ilmiah Wahana Pendidikan, 2025)
Dispute Settlement Body (DSB) as a dispute settlement body of the World Trade Organization (WTO) in the trade dispute between Indonesia and the European Union in the case of nickel ore export restrictions loaded by the Indonesian Government through domestic policies. Thus, on 22 November 2019 the European Union officially sued Indonesia to the WTO with violations of Article X, Article XI and could not be justified by Article XI Paragraph (2) point (a) of GATT 1994 and Article XX point (d) of GATT 1994, and the European Union claimed that Article III Paragraph (1) point (b) of the Agreement on Subsidies and Countervailing Measures (SCM) was not consistent. In the end, the Panel granted the EU's lawsuit against Indonesia through the Final Report of the Panel DS592 by recommending Indonesia to cancel the nickel ore export ban policy. The research method in this case uses a normative legal approach. Normative law in this research has two legal sources, namely primary and secondary legal sources. Primary legal sources refer to Dispute Settlement Body Decision Number DS592, the 1994 GATT Agreement, Minister of Energy and Mineral Resources Regulation No. 1 of 2014, and Minister of Energy and Mineral Resources Regulation No. 11 of 2019. Then, secondary legal sources refer to a book by Huala Adolf entitled International Trade Law and a book by Serlika Aprika and Rio Adhitya entitled International Trade Law. The results of this study indicate that the DSB decision through the Final Report of the Panel number DES592 does not have binding legal force for the Indonesian state and will not have any legal consequences on Indonesia's legal sovereignty. Because the decision is considered to have experienced errors in terms of interpreting Indonesia's nickel ore export ban policy in relation to the applicable rules in the GATT 1994. Thus, Indonesia demands that the WTO form an Appealate Body to appeal the DSB decision